PERANCANGAN LOKAL LATIHAN KERJA DI KABUPATEN BOLAANG MONGONDOW SELATAN DENGAN PENDEKATAN ARSITEKTUR KONTEKSTUAL - Manyo, Handi; Siola, Amru; Arifuddin, Ariffuddin (Program Studi Teknik Arsitektur, Fakultas Teknik - Universitas Ichsan Gorontalo, 2024)
The local design for the South Bolaang Mongondow Job Training, which is located in Bolaang Uki District, Molibagu Village, aims to meet the need for better manpower training facilities, roles and functions in various fields, physical and non-physical qualities, facilities and management. The reason for the design by applying the Contextual Architecture approach is to present buildings that pay attention to their surrounding conditions so that their existence is harmonious and unified, and thus the potential in the environment i s not i gnored. Keywords : Local work exercises, Local Designing work exercises, Contextual architecture